Balios Eulophid Baeoentedon balios Wang, Huang & Polaszek (Insecta: Hymenoptera: Eulophidae) - Muhammad Z. Ahmed; Yisell Velazquez Hernandez; Antonio Francis; Gregory Evans; Eric Rohrig; Lance S. Osborne; Catharine Mannion (EDIS)
This EDIS publication is an alternate version of a page published first on the Featured Creatures website. The Featured Creatures collection provides in-depth profiles of insects, nematodes, arachnids and other organisms relevant to Florida. These profiles are intended for the use of interested laypersons with some knowledge of biology as well as academic audiences. This 5-page fact sheet that discusses Baeoentedon balios was written by Muhammad Z. Ahmed, Yisell Velazquez Hernandez, Antonio Francis, Gregory Evans, Eric Rohrig, Lance Osborne, and Catharine Mannion, and published by the UF Entomology and Nematology Department, March 2017.